2012
DOI: 10.1007/s11999-011-2047-z
|View full text |Cite
|
Sign up to set email alerts
|

Endoprosthetic Treatment is More Durable for Pathologic Proximal Femur Fractures

Abstract: Background Pathologic proximal femur fractures result in substantial morbidity for patients with skeletal metastases. Surgical treatment is widely regarded as effective; however, failure rates associated with the most commonly used operative treatments are not well defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
128
3
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(151 citation statements)
references
References 15 publications
12
128
3
4
Order By: Relevance
“…We also believe that performing surgery semielectively for prophylactic purposes may provide less inherent risk for complications than operating on a fracture and performing unplanned surgery urgently, which was reported in one fracture study [3]. Steensma et al [21,22] reported that patients sustaining a pathologic fracture treated with arthroplasty had fewer treatment failures and revision surgeries than those treated with internal fixation. Because of improved outcomes with arthroplasty in pathologic fractures, trends are shifting toward treating more patients with pathologic fractures with joint replacements (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…We also believe that performing surgery semielectively for prophylactic purposes may provide less inherent risk for complications than operating on a fracture and performing unplanned surgery urgently, which was reported in one fracture study [3]. Steensma et al [21,22] reported that patients sustaining a pathologic fracture treated with arthroplasty had fewer treatment failures and revision surgeries than those treated with internal fixation. Because of improved outcomes with arthroplasty in pathologic fractures, trends are shifting toward treating more patients with pathologic fractures with joint replacements (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Postoperatively, the median total MSTS score (measured at most recent followup) for the entire group of patients was 21 (range, , the median ECOG score was 2 (range, 0-3, 68% B 2), and the median KPS score was 60 (range, 40-100). For the 11 patients with at least 1 year of followup, the median total MSTS score (measured at most recent followup) was 27 (range, [21][22][23][24][25][26][27][28][29][30], the median ECOG score was 1 (range, 0-2, 100% B 2), and the median KPS score was 80 (range, 60-100). For the remaining 11 patients with less than 1 year of followup, the median total MSTS score (measured at most recent followup) was 11 (range, 5-25), the median ECOG score was 3 (range, 1-3, 36% B 2), and the median KPS score was 40 (range, 40-80).…”
mentioning
confidence: 99%
“…We reviewed the peer-reviewed literature from 1980 through 2011 and found 14 articles describing outcomes for IMN, PFRR, LSCH/CH, and ORIF in patients treated for femoral metastases. Notably, few studies examined proximal femur fractures specifically, and 14 of 15 studies were retrospective, citing either a retrospective cohort (Level of Evidence IV) or retrospective comparison design (Level of Evidence III) (Table 5) [2,4,5,[7][8][9][10][11][12][13][14][15][18][19][20]. A single, prospective study (Level I) was found that showed functional improvement in patients undergoing surgery for nonspinal bone metastases [17], but outcomes specific to the proximal femur were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Operative strategies for the treatment of pathologic proximal femur fractures include the use of intramedullary fixation (IMN) [13,19], extramedullary, plate-screw fixation (open reduction and internal fixation [ORIF]) [5], and endoprosthetic reconstruction (proximal femur resection reconstruction [PFRR] or long-stem cemented hemiarthroplasty/ cemented hemiarthroplasty [LSCH/CH]) [9,19]. Retrospective data support the use of each approach, but few attempts have been made to rigorously compare treatment outcomes [15,19]. An extensive list of patient-or treatment-related factors often is considered when selecting an operative strategy and includes estimated patient survival, the necessity of a separate tumor resection procedure, the method of tumor resection (eg, intralesional versus wide resection), sensitivity of the lesion to radiation therapy or chemotherapy, baseline health and performance status, type of cancer, the extent of osseous and/or visceral metastasis, anatomic region(s) of femoral involvement, and the perceived risk of procedure-specific complications.…”
Section: Introductionmentioning
confidence: 99%